Coping efficacy in athletes and its relationship to coping strategies - Wang, W.; Chi, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The main purpose of this research was to develop a tool for the measurement of coping efficiency in athletes. With the use of a literature review and interviews, a preliminary scale was developed with 48 items, which were divided into 3 dimensions. These included: `means-end belief`, `control belief` and `agent belief`. In total, 623 college athletes were tested, including 412 males and 211 females. After being reviewed twice, the final scale was made up of 16 items, using the same3 dimensions. The scale demonstrated good internal consistency, test-retest reliability, content validity, construct validity and concurrent validity. Results / Discussion The results showed that gender differences were found in all 3 dimensions through the use of a MANOVA Competition level differences were only found for the `means-end belief` and `agent belief` dimensions. No athletic sport differences were found in any of the dimensions. Correlational analysis showed differing degrees of positive correlation between coping methods and coping efficacy. The results showed a significant correlation between both problem-focused coping and emotion-focused coping and all three of the dimensions of coping efficacy. There was also a significant correlation between `control belief` and each of the four coping methods. Avoidant or transcendant styles of coping were found to have poor correlation with `agent belief`, but a significant correlation with the `means-end belief`. According to the results of the research, the constructed tool for measuring coping efficacy in athletes is of high validity and efficiency, and could be used in future research in this field.